Assessment of the nutritional status of children aged 6-59 Months: case of internally displaced persons of Cabo Delgado, Northern Mozambique (Research, Society and Development, 2022)
Introduction: Nutritional status is the balance between nutrient supply and energy expenditure, an indicator linked to children's health. In Cabo Delgado, northern Mozambique, conflicts caused by non-state armed groups since 2017 cause many displacements of the population that have negative consequences on quality of life, with child malnutrition prevalent and representing about 45% of deaths among children. The aim of this study was to evaluate the nutritional status of children aged 6-59 months internally displaced from Cabo Delgado in northern Mozambique. Methodology: descriptive and cross-sectional observational study with quantitative approach carried out at the Corane resettlement center in nampula province that welcomes most of the displaced from Cabo Delgado. Anthropometric data were measured from 150 children aged 6-59 months and then applied a questionnaire to their parents. The data were treated using descriptive statistics in SPSS version 26.0 and Microsoft Office Excel 2016. Results: Of the 150 participants, 53.3% were female and 46.7% male. Regarding nutritional status using the weight/height index, 62.0% of the children were eutrophic, 20.7% with moderate acute malnutrition, 16.6% severe acute malnutrition and 0.7% were overweight. Conclusion: Despite the displacement, most of the children evaluated were eutrophic, which can result from various types of support they receive from humanitarian organizations, civil society and the government, as well as the practice of activities related to survival strategies.